Effect of Residual Bacteria on the Outcome of Pulp Regeneration In Vivo. (January 2017) - Verma, P.; Nosrat, A.; Kim, J.R.; Price, J.B.; Wang, P.; Bair, E.; Xu, H.H.; Fouad, A.F.
It is not known to what extent residual infection may interfere with the success of pulp regeneration procedures. The aim of this study was to determine, radiographically and histologically, the effect of residual bacteria on the outcome of pulp regeneration mediated by a tissue-engineered construct as compared with traditional revascularization. Periapical lesions were induced in 24 canine teeth of 6 ferrets. After disinfection with 1.25% NaOCl and triple antibiotic paste, ferret dental pulp stem cells, encapsulated in a hydrogel scaffold, were injected into half the experimental teeth. The other half were treated with the traditional revascularization protocol with a blood clot scaffold. After 3 mo, block sections of the canine teeth were imaged radiographically and processed for histologic and histobacteriologic analyses. Associations between variables of interest were evaluated through mixed effects regression models. There were no significant differences between the 2 experimental groups in radiographic root development ( P > 0.05). There was a significant association between the presence of persistent periapical radiolucency and root wall thickness ( P = 0.02). There was also no significant difference in histologic findings between the 2 experimental groups ( P > 0.05). The presence of residual bacteria was significantly associated with lack of radiographic growth ( P < 0.001). The amount of dentin-associated mineralized tissue formed in teeth with residual bacteria was significantly less than in teeth with no residual bacteria ( P < 0.001). Residual bacteria have a critical negative effect on the outcome of regenerative endodontic procedures.